Locus of control, social support, and resilience among pregnant women experiencing partner violence - Hasselle, Amanda J. (Journal of family violence, 2023)
Purpose: Intimate partner violence (IPV) has significant consequences for women’s mental and physical health, but many women show adaptive functioning amidst this adversity. Few studies have assessed the interactive internal and external resources that promote resilience among IPV-exposed pregnant women. The current study examined associations between locus of control (LOC), social support (family/friend), and resilience in IPV-exposed pregnant women, as well as the moderating role of social support on the association between LOC and resilience. Method: Pregnant women (N = 137; MAge=27.30, SD = 6.00; 66% Black/African American) who experienced IPV in the previous year completed a series of self-report measures during a structured 1.5-hour assessment. Direct and moderating relations were examined using hierarchical linear regression analyses. Results: The family support model was significant (F = 3.53, p = .003, R2 = 14.0%), with more internal LOC (B=-1.28, p = .011) and more family support (B = 0.53, p = .019) associated with higher resilience. Including the LOC by family support interaction significantly improved (∆F = 7.34, p = .008, ∆R2 = 4.6%) the model (F = 4.22, p < .001, R2 = 18.6%). The interaction term was significant (B = 0.23, p = .008), such that more external LOC was associated with lower resilience only among women with low family support (t=-3.81, p < .001). The friend support model was significant (F = 5.64, p < .001, R2 = 20.6%). More internal LOC (B=-1.28, p = .008) and more friend support (B = 0.74, p < .001) were associated with higher resilience. Adding the LOC by friend support interaction did not significantly improve the model. Conclusion: Results suggest that internal LOC and social support are associated with higher resilience and that strong family supports may buffer against the negative consequences typically associated with external LOC.